Australian Research in Infection Prevention and Control: A Bibliometric Review From the Past Two Decades - Mitchell, Brett; Matterson, Georgia; Carroll, Matthew; Stewardson, Andrew; Tehan, Peta (Elsevier BV, 2026)
Background Australia is recognised as a leading contributor to infection prevention and control (IPC) randomised controlled trials. However, the broader landscape of Australian IPC research has not been comprehensively mapped. This bibliometric review examined research trends, thematic focus areas, and methodological approaches in Australian IPC research over the past two decades. Methods A systematic search of Scopus identified IPC-related documents from January 2003 to September 2025. Eligible documents reported original IPC research involving an Australian population and included at least one author with an Australian institutional affiliation. Reviews required an Australian author. Following screening in Covidence, metadata from included documents were analysed using the web application Biblioshiny® to assess publication trends, citation patterns, authorship networks, and international collaboration. Manual thematic coding was undertaken, and reporting followed the BIBLIO checklist. Results A total of 841 documents from 241 sources were included in the analysis. Publication output increased notably from 2013 onward, with further growth during 2020–2021 and again in 2025. Surveillance was the most common research theme (18.2% [153/841]). Observational designs dominated the literature (44.9% [378/841]), while randomised controlled trials accounted for just 1.2% (10/841) of documents. There was extensive international collaboration, involving authors from 81 countries. Conclusion Australian IPC research output has expanded considerably but remains concentrated within a limited number of themes and is dominated by single-centre observational studies. These findings highlight opportunities to diversify methodologies, strengthen evidence quality, and better align future research with IPC practice and policy priorities.
Keywords: Infection control; Cross-infection; Nursing; Australia